Valproate in the treatment of epilepsy in girls and women of childbearing potential. (16th May 2015) - Tomson, Torbjörn; Marson, Anthony; Boon, Paul; Canevini, Maria Paola; Covanis, Athanasios; Gaily, Eija; Kälviäinen, Reetta; Trinka, Eugen
Summary This document provides guidance on the use of valproate in girls and women of childbearing age from a joint Task Force of the Commission on European Affairs of the International League Against Epilepsy (CEA‐ILAE) and the European Academy of Neurology (EAN), following strengthened warnings from the Coordination Group for Mutual Recognition and Decentralised Procedures‐Human (CMDh) of the European Medicines Agency (EMA), which highlight the risk of malformations and developmental problems in infants who are exposed to valproate in the womb. To produce these recommendations, the Task Force has considered teratogenic risks associated with use of valproate and treatment alternatives, the importance of seizure control and of patient and fetal risks with seizures, and the effectiveness of valproate and treatment alternatives in the treatment of different epilepsies. The Task Force's recommendations include the following: (1) Where possible, valproate should be avoided in women of childbearing potential. (2) The choice of treatment for girls and women of childbearing potential should be based on a shared decision between clinician and patient, and where appropriate, the patient's representatives. Discussions should include a careful risk–benefit assessment of reasonable treatment options for the patient's seizure or epilepsy type. (3) For seizure (or epilepsy) types where valproate is the most effective treatment, the risks and benefits of valproate and other treatment alternatives should be discussed. (4) Valproate should not be prescribed as a first‐line treatment for focal epilepsy. (5) Valproate may be offered as a first‐line treatment for epilepsy syndromes where it is the most effective treatment, including idiopathic (genetic) generalized syndromes associated with tonic–clonic seizures. (6) Valproate may be offered as a first‐line treatment in situations where pregnancy is highly unlikely (e.g., significant intellectual or physical disability). (7) Women and girls taking valproate require regular follow‐up for ongoing consideration of the most appropriate treatment regimen.